A Rapidly Fatal Case of Low-Dose Methotrexate Toxicity - Shaikh, Nasreen (Case Rep Med, 2018)
An 82-year-old female presented with multiple oral ulcers and malena for 1 week. Her laboratory tests revealed pancytopenia and acute renal failure. She had history of rheumatoid arthritis for which she was taking 7.5 mg methotrexate weekly and stage 4 chronic kidney disease from diabetic nephropathy. During the hospital stay, she developed pneumonia and septic shock requiring norepinephrine and vasopressin. She underwent continuous venovenous hemodiafiltration. Leucovorin, filgrastim, and multiple packed red blood cell and platelet transfusions were given. She remained hypotensive and pancytopenic despite all interventions. She died on day 6 of hospital stay from acute hypoxic respiratory failure due to septic shock.